PENGARUH STORE ATMOSPHERE, HEDONIC SHOPPING, DAN PROMOSI TERHADAP IMPULSIVE BUYING - Rindyah Hanafi (Universitas Merdeka Madiun, 2019)
This study aims to determine the influence of store atmosphere, hedonic shopping, and partial and simultaneous promotion of impulsive buying conducted in the modern retail community in Madiun City. The population in this study is the consumers of various selected big retails in Madiun City, namely Matahari Department Store Madiun Plaza and Sun City Mall, Carrefour, Ramayana and Samudra Swalayan. In this study, the number of population is not known with certainty, so in this study the number of samples used is determined based on the model estimation interval model for the parameter of proportion P, so that the sample obtained as many as 100 people. The sampling technique used in this research is by using purposive convenience sampling technique. Data analysis techniques use classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing by using t test and F test. The findings were obtained: (1) Store atmosphere partially influence to impulsive buying done by society in modern retail in Madiun City. (2) Hedonic shopping partially affects the impulsive buying done by society in modern retail in Madiun City. (3) Promotion partially influence to impulsive buying done by society in modern retail in Madiun City. (4) Store atmosphere, hedonic shopping, and promotion simultaneously affect the impulsive buying done in the modern retail community in Madiun CityÂ Store Atmosphere, Hedonic Shopping, Promotion, Impulsive Buying